Urbanization-globalization-CO2 emissions nexus revisited: empirical evidence from South Africa. Issue 6 (June 2019) - Salahuddin, Mohammad; Gow, Jeff; Ali, Md. Idris; Hossain, Md. Rahat; Al-Azami, Khaleda Shaheen; Akbar, Delwar; Gedikli, Ayfer
Abstract: The environmental effects of urbanization and globalization are still subject to debate among scholars. South Africa is the most globalized, most urbanized and the most carbon-intensive economy in Sub Saharan Africa (SSA) region. Taking this into cognizance, this study examines the effects of urbanization and globalization on CO2 emissions for South Africa using time series annual data for the period 1980–2017. Zivot and Andrews single and Bai and Perron multiple structural break unit root tests are employed to assess if all the series are stationary. This procedure follows ARDL cointegration test to check the presence of a long-run association among variables. Having been confirmed about such a cointegrating relation, ARDL short-run and long run coefficients indicate that urbanization induces CO2 emissions while only long-run significant emissions effect of globalization was noted. Toda-Yamamoto non-causality test reports a bi-directional causal link between urbanization and CO2 emissions. No causal link is observed between globalization and CO2 emissions. Variance decomposition results do not rule out these effects in future. Policy implications are discussed.